Longitudinal profiles of highly sensitive hepatitis B surface antigen levels: re‐evaluation of HBsAg seroclearance. (5th November 2015) - Seto, Wai‐Kay; Tanaka, Yasuhito; Wong, Danny K.‐H.; Shinkai, Noboru; Cheung, Ka‐Shing; Liu, Kevin S.‐H.; Fung, James; Lai, Ching‐Lung; Yuen, Man‐Fung
Abstract: Background & Aims: Serologic profiles after hepatitis B surface antigen (HBsAg) seroclearance in chronic hepatitis B (CHB) have not been well‐studied. Methods: We employed a highly sensitive HBsAg (hs‐HBsAg) assay (lower detection limit 0.5 mIU/ml), 100 times more sensitive than conventional HBsAg measurements. CHB patients achieving HBsAg seroclearance defined by conventional assays were followed up for serum hs‐HBsAg, HBV DNA and antibody to HBsAg (anti‐HBs) levels at 0 months, 6–12 months and 3–5 years after HBsAg seroclearance. Factors associated with hs‐HBsAg detectability were determined. Results: One hundred and nine patients were recruited; 94 (86.2%) were followed up to years 3–5; and 25 patients (22.9%) were on nucleoside analogue therapy for a median duration of 6.0 (range 1.5–12.7) years before HBsAg seroclearance. Detectable hs‐HBsAg was noted in 88 (80.7%), 60 (55.0%) and 20 (21.3%) patients at 0 months, 6–12 months and 3–5 years respectively. At years 3–5, genotype B patients, when compared to genotype C patients, had a higher anti‐HBs positive rate (63.2% and 41.1% respectively, P = 0.036). Serum anti‐HBs positivity, when compared to persistent anti‐HBs negativity, was associated with a lower rate of hs‐HBsAg detection (7.4% and 40% respectively, P < 0.001). Multivariate analysis showed anti‐HBs negativity at years 3–5 to be independently associated with persistently positive hs‐HBsAg ( P = 0.007, odds ratio 7.1, 95% confidence interval 1.7–29.3). Conclusion: Serum hs‐HBsAg could detect HBsAg presence in a substantial proportion of CHB after HBsAg seroclearance defined by conventional assays, especially among anti‐HBs negative individuals. Serum hs‐HBsAg could potentially assist differentiating HBsAg‐negative CHB from individuals with only past HBV exposure without carrier state.